(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2009)
The article presents the problem of formation of cognitive interest to lessons of the Ukrainian language in elementary school. The interest of elementary school pupils by the native language is a long process, which is carried out systematically and stage by stage. Proof cognitive interest is formed in unity of emotional, rational and effective in learning.